Short hairpin RNA targeting insulin-like growth factor binding protein-3 restores the bioavailability of insulin-like growth factor-1 in diabetic rats - Zhou,Zhang-Yan (2016)
ABSTRACT Purpose To investigate whether intracavernosal injection of short hairpin RNA for IGFBP-3 could improve erectile function in streptozotocin-induced diabetic rats. Materials and methods After 12 weeks of IGFBP-3 short hairpin RNA injection treatment, intracavernous pressure responses to electrical stimulation of cavernous nerves were evaluated. The expression of IGFBP-3 and IGF-1 at mRNA and protein levels were detected by quantitative real-time PCR analysis and Western blot, respectively. The concentration of cavernous cyclic guanosine monophosphate was detected by enzyme-linked immunosorbent assay. Results At 12 weeks after intracavernous administration of IGFBP-3 shRNA, the cavernosal pressure was significantly increased in response to the cavernous nerves stimulation compared to the diabetic group (P<0.05). Cavernous IGFBP-3 expression at both mRNA and protein levels was significantly inhibited. At the same time, cavernous IGF-1 expression was significantly increased in the IGFBP-3 shRNA treatment group compared to the diabetic group (P<0.01). Cavernous cyclic guanosine monophosphate concentration was significantly increased in the IGFBP-3 shRNA treatment group compared to the diabetic group (P<0.01). Conclusions Gene transfer of IGFBP-3 shRNA could improve erectile function via the restoration of cavernous IGF-1 bioavailability and an increase of cavernous cGMP concentration in the pathogenesis of erectile dysfunction in streptozotocin-induced diabetic rats.